2019
DOI: 10.1016/j.fertnstert.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extended blastocyst exposure of hyaluronan enriched transfer media on implantation rate in frozen embryo transfers

Abstract: Prospective cohort study. MATERIALS AND METHODS: We followed 93,775 women participating in the Nurses' Health Study II between 1991 and 2013 who had no prior history of cardiovascular disease, cancer, or diabetes and who reported the usual length and regularity of their menstrual cycles at ages of 14-17, 18-22, and 28-48 years. We obtained hazard ratios (HR) and 95% confidence intervals (CI) for the relationships between menstrual cycle characteristics and mortality from Cox proportional hazards models adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An inflated concentration of hyaluronan improves in-vitro growth and the number of cells in bovine embryos by increasing the viscosity of the culture medium. They also discovered that embryos cultivated with hyaluronan supplementation had greater survival rates following freezing [ 1 - 3 , 10 , 11 ]. Onestep with increased hyaluronic acid concentration can be used successfully as a macromolecule in a medium used for embryo transfer which gives outcome in high pregnancy and implantation rates in a recent study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inflated concentration of hyaluronan improves in-vitro growth and the number of cells in bovine embryos by increasing the viscosity of the culture medium. They also discovered that embryos cultivated with hyaluronan supplementation had greater survival rates following freezing [ 1 - 3 , 10 , 11 ]. Onestep with increased hyaluronic acid concentration can be used successfully as a macromolecule in a medium used for embryo transfer which gives outcome in high pregnancy and implantation rates in a recent study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Perez et al showed that increased exposure to EmbryoGlue had a positive impact on implantation rate and clinical pregnancy rate, with a statistically significant difference seen in subgroup analysis between exposure times of 1 hour and 2 or 3 hours to HETM (p < 0.05, n ¼ 119). 23 A recent Cochrane review reported the effects of adherence compound HA when used in functional concentrations in embryo transfer media (21 studies and 6,704 participants). 24 This review found that there is evidence to support improved clinical pregnancy and live birth rates with the use of HA in embryo transfer media compared with low concentration or no HA media (Relative Risk (RR): 1.21, 95% CI: 1.1-1.31, 10 randomized controlled trials, N ¼ 4,066, I 2 ¼ 33%, moderate-quality evidence), although it is important to note that the observed increase in multiple pregnancy rates is suggested to be due to embryo transfer policies rather than the HA supplementation.…”
Section: Recent Evidencementioning
confidence: 99%